PENGARUH PEMBERIAN MULTI MODAL ANALGESIA INTRA ANESTESI TERHADAP STABILITAS TEKNANAN DARAH PASIEN SELAMA OPERASI - Fahria Nur Maulida; Miftahul Khoeriyah; Nidaul Khaira; Ratih Kusuma Dewi (Jurnal Riset Multidisiplin Edukasi, 2025)
Background: Blood pressure stability during surgery is essential to prevent anesthetic complications caused by pain and surgical stress. Multimodal intra-anesthetic analgesia, which combines analgesic drugs with different mechanisms of action, has been shown to help maintain hemodynamic stability. Several studies report that combinations of dexmedetomidine, lidocaine, ketamine, paracetamol, and magnesium sulfate can reduce blood pressure fluctuations and inhalation anesthetic requirements. Objective: This literature review aims to analyze the effect of multimodal intra-anesthetic analgesia on blood pressure stability in surgical patients based on studies published between 2023 and 2025. Methods: A literature review was conducted using 10 scientific journals (six national and four international) from credible sources. The analysis focused on study design, analgesic interventions, blood pressure parameters, and intraoperative hemodynamic outcomes. Results: The review demonstrates that multimodal intra-anesthetic analgesia effectively maintains intraoperative blood pressure stability. Compared with opioid-based analgesia alone, multimodal approaches consistently reduced blood pressure fluctuations and anesthetic requirements.